TURNING THE FLASHLIGHT ON HUMAN RESOURCES IN SCHOOLS: A CASE STUDY IN A SECONDARY SCHOOL IN MAURITIUS - Nathalie, Congo; Swaleyah, Beebeejaun (PEOPLE: International Journal of Social Sciences, 2017)
All leaders irrespective of in the sector in which they are to have fulfill a set of core leadership practices. This is also true of educational leaders. These will help them to lead their schools in an effective way. Hence, they have to set directions. They also have to develop human resources, refine and align the organization. Furthermore, they have to promote and participate in teacher learning and development. Next, they have to ensure an orderly and supportive environment. Until now, much attention has been given to four of these core practices, but little has been written on the fifth one which consists of developing the human resources in schools. This practice is important as it involves building capacity which in turn leads to collective efficacy. This enables the human resources to contribute greatly in the school improvement process. This paper discusses key findings from a research on how teachers define the attempts of the educational leader in developing human resources. Data has been gathered by using a questionnaire (n = 62) and semi-structured interviews (n = 7). Findings hint at the fact that educational leaders are not very successful in developing their human resources. It is also found that the educational leader does not allocate enough means to developing human resources. The article concludes with several implications which could help to enhance educational leaders’ effectiveness in developing human resources.